Violence Against Women: Looking Behind the Mask of Incarcerated Batterers - Irene C. Baird (Adult Education Research Conference, 2000)
Addressing violence against women by sharing battered prison women's written accounts with incarcerated male abusers, in a Freirian/humanities adult education program, confirmed the feminist perspective of male entitlement, female subordination in a sociohistorical context.